Binding of Rap1 and Riam to Talin1 Fine-Tune β2 Integrin Activity During Leukocyte Trafficking - Bromberger, Thomas; Klapproth, Sarah; Rohwedder, Ina; Weber, Jasmin; Pick, Robert; Mittmann, Laura; Min-Weißenhorn, Soo Jin; Reichel, Christoph A.; Scheiermann, Christoph; Sperandio, Markus; Moser, Markus (Frontiers in Immunology, 2021)
β2 integrins mediate key processes during leukocyte trafficking. Upon leukocyte activation, the structurally bent β2 integrins change their conformation towards an extended, intermediate and eventually high affinity conformation, which mediate slow leukocyte rolling and firm arrest, respectively. Translocation of talin1 to integrin adhesion sites by interactions with the small GTPase Rap1 and the Rap1 effector Riam precede these processes. Using Rap1 binding mutant talin1 and Riam deficient mice we show a strong Riam-dependent T cell homing process to lymph nodes in adoptive transfer experiments and by intravital microscopy. Moreover, neutrophils from compound mutant mice exhibit strongly increased rolling velocities to inflamed cremaster muscle venules compared to single mutants. Using Hoxb8 cell derived neutrophils generated from the mutant mouse strains, we show that both pathways regulate leukocyte rolling and adhesion synergistically by inducing conformational changes of the β2 integrin ectodomain. Importantly, a simultaneous loss of both pathways results in a rolling phenotype similar to talin1 deficient neutrophils suggesting that β2 integrin regulation primarily occurs via these two pathways.